Cryo-tomography and 3D Electron Diffraction Reveal the Polar Habit and Chiral Structure of the Malaria Pigment Crystal Hemozoin - Klar, Paul Benjamin; Waterman, David Geoffrey; Gruene, Tim; Mullick, Debakshi; Song, Yun; Gilchrist, James Boris; Owen, C David; Wen, Wen; Biran, Idan; Houben, Lothar; Regev-Rudzki, Neta; Dzikowski, Ron; et al. (ACS central science, 2024)
Detoxification of heme in Plasmodium depends on its crystallization into hemozoin. This pathway is a major target of antimalarial drugs. The crystalline structure of hemozoin was established by X-ray powder diffraction using a synthetic analog, β-hematin. Here, we apply emerging methods of in situ cryo-electron tomography and 3D electron diffraction to obtain a definitive structure of hemozoin directly from ruptured parasite cells. Biogenic hemozoin crystals take a striking polar morphology. Like β-hematin, the unit cell contains a heme dimer, which may form four distinct stereoisomers: two centrosymmetric and two chiral enantiomers. Diffraction analysis, supported by density functional theory analysis, reveals a selective mixture in the hemozoin lattice of one centrosymmetric and one chiral dimer. Absolute configuration has been determined by morphological analysis and confirmed by a novel method of exit-wave reconstruction from a focal series. Atomic disorder appears on specific facets asymmetrically, and the polar morphology can be understood in light of water binding. Structural modeling of the heme detoxification protein suggests a function as a chiral agent to bias the dimer formation in favor of rapid growth of a single crystalline phase. The refined structure of hemozoin should serve as a guide to new drug development.